2018
DOI: 10.1177/1010539518800339
|View full text |Cite
|
Sign up to set email alerts
|

Current Smoking Behavior Among Medical Students in Mainland China: A Systematic Review and Meta-Analysis

Abstract: This study aimed to estimate the prevalence of current smoking among medical students in mainland China through a systematic search across 6 electronic databases for English or Chinese studies published before May 25, 2018. A total of 79 studies were included; 26 had a high risk of bias. The overall pooled prevalence of current smoking was 10.93% (7460/68 253; 95% confidence interval = 0.09%, 13.08%, I2 = 98.6%). This study found a decreasing prevalence of current smoking over the period studied (survey year r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…is finding is similar to studies carried out globally with smoking prevalence reported at the University of East Africa as 9.02% [35]. Meta-analyses from Mainland Chinese and from the Kingdom of Saudi Arabia reported, respectively, university student smoking prevalence at 10.83% [36] and 17% [37]. ose articles were specific to medical and health science college students.…”
Section: Discussionsupporting
confidence: 87%
“…is finding is similar to studies carried out globally with smoking prevalence reported at the University of East Africa as 9.02% [35]. Meta-analyses from Mainland Chinese and from the Kingdom of Saudi Arabia reported, respectively, university student smoking prevalence at 10.83% [36] and 17% [37]. ose articles were specific to medical and health science college students.…”
Section: Discussionsupporting
confidence: 87%
“…Compared with other European students, Italian medical students show the second highest rate of smoking [ 53 ]. A systematic review by Niu [ 54 ] on a Chinese population of medical students found some improvements in the status of tobacco use, following an educational campaign against tobacco targeted to medical students. Moreover, while the prevalence of smoking is about 20% in the Italian general population, it is slightly higher (ranging between 15–31%) in Italian medical student population [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…People who reported having smoked fewer than 100 cigarettes in their lives were classified as never smokers, and the remainder were asked whether they were current or former smokers. 24,25 Physical activity was assessed using the Korean version of the long-format International Physical Activity Questionnaire. 26 Responses were divided into 2 categories: participants who engaged in at least 150 minutes of moderate-intensity aerobic physical activity per week, at least 75 minutes of vigorous-intensity aerobic activity per week, or a combination of moderate-and vigorous-intensity physical activity (eg, 1 minute of vigorous-intensity physical activity and 2 minutes of moderate-intensity physical activity) for at least 75 minutes per week were classed as engaging in aerobic physical activity, and those who did not were classed as not engaging in aerobic physical activity.…”
Section: Covariatesmentioning
confidence: 99%